PERBANDINGAN KINERJA KEUANGAN PERBANKAN UMUM KONVENSIONAL DAN PERBANKAN UMUM SYARIAH YANG TERDAFTAR DI OJK - Syahrani, Alfi; Wahyuni, Asri Nur (Magister Manajemen STIE Bank BPD Jateng, 2024)
The banking sector is one part that plays an important role in the country's efforts to increase economic growth and development. The aim of this research is to compare the development of the financial performance of conventional general banking and sharia general banking. The basic population of this research are banks registered on the BEI (Indonesian Stock Exchange), and the sample consists of 6 conventional commercial banks and 2 sharia commercial banks. In this research, the SPSS version 26 test tool was used with Descriptive Analysis Test, Normality Test, Homogeneity Test and Hypothesis Test. The results of this research show that in terms of CAR (Capital Adequacy Ratio), ROA (Return On Assets), BOPO (Operating Costs, Operating Income) and NPL/NPF (Non-performing loans/non-performing finance) there is no difference in performance in conventional and general banking. sharia general banking. Meanwhile, in the LDR/FDR ratio (Loan To Deposit Ratio/Financing To Deposit Ratio) there are differences in the performance of conventional general banking and sharia general banking